Infective Native Aortic Aneurysm: a Delphi Consensus Document on Treatment, Follow Up, and Definition of Cure - Wyss, Thomas R; Giardini, Matteo; Sörelius, Karl (European journal of vascular and endovascular surgery, 2024)
OBJECTIVE: Evidence is lacking to guide the management of infective native aortic aneurysm (INAA). The aim of this study was to establish expert consensus on surgical and antimicrobial treatment and follow up, and to define when an INAA is considered cured. METHODS: Delphi methodology was used. The principal investigators invited 47 international experts (specialists in infectious diseases, radiology, nuclear medicine, and vascular and cardiothoracic surgery) via email. Four Delphi rounds were performed, three weeks each, using an online questionnaire with initially 28 statements. The panellists rated the statements on a five point Likert scale. Comments on statements were analysed, statements were revised and added or deleted, and the results were presented in the iterative rounds. Consensus was defined as ≥ 75% of the panel rating a statement as strongly agree or agree on the Likert scale, and consensus on the final assessment was defined as Cronbach's alpha > 0.80. RESULTS: All 49 panellists completed all four rounds, resulting in 100% participation. One statement was added based on the results and comments of the panel, resulting in 29 final statements: three on need for consensus, 20 on treatment, five on follow up, and one on definition of cure. All 29 statements reached agreement of ≥ 86%. Cronbach's alpha increased for each consecutive round; round 1, 0.85; round 2, 0.90; round 3, 0.91; and round 4, 0.94. Thus, consensus was reached for all statements. CONCLUSION: INAAs are rare, and high level evidence to guide optimal management is lacking. This consensus document was established with the aim of helping clinicians manage these challenging patients, as a supplement to current guidelines. The presented consensus will need future amendments in accordance with newly acquired knowledge.
Keywords: delfská metoda; konsensus; Aortic Aneurysm; aortální aneurysma; Consensus; Humans; Follow-Up Studies; lidé; Delphi Technique; následné studie